Recombinant human deoxyribonuclease for the treatment of acute asthma in children. Issue 2 (3rd August 2007) - Boogaard, R; Smit, F; Schornagel, R; Vaessen-Verberne, A A P H; Kouwenberg, J M; Hekkelaan, M; Hendriks, T; Feith, S W W; Hop, W C J; de Jongste, J C; Merkus, P J F M
Abstract : Background: Airway obstruction in acute asthma is the result of airway smooth muscle contraction, inflammation and mucus plugging. Case reports suggest that mucolytic therapy might be beneficial in acute asthma. The aim of this study was to determine the efficacy of the mucolytic drug recombinant human deoxyribonuclease (rhDNase) in addition to standard treatment at the emergency department in children with an asthma exacerbation. Methods: In a multicentre randomised double-blind controlled clinical trial, 121 children brought to the emergency room for a moderate to severe asthma exacerbation were randomly assigned to receive either a single dose of 5 mg nebulised rhDNase or placebo following the second dose of bronchodilators. An asthma score (scale 5–15) was assessed at baseline and at 1, 2, 6, 12 and 24 h. The primary outcome variable was the asthma score 1 h after the study medication. Results: One hour after the study medication the asthma score in the rhDNase group showed an adjusted mean decrease from baseline of 1.0 (95% CI 0.5 to 1.6) points compared with 0.7 (95% CI 0.3 to 1.2) points in the placebo group (mean difference 0.4 (95% CI −0.2 to 1.0) points; p = 0.23). The asthma score over the study period of 24 h also did not differ significantly between the rhDNase and placebo group (mean difference 0.2 (95% CI −0.3 to 0.7) points, p = 0.40). The duration of oxygen supplementation and number of bronchodilator treatments in the first 24 h were similar in both groups. Conclusion: Adding a single dose of nebulised rhDNase to standard treatment in the emergency room has no beneficial effects in children with moderate to severe acute asthma.